Attitudes of Wannabe Kinesiology Students about School Subjects, School in General and Extracurricular Learning : Stavovi studenata koji žele studirati kineziologiju prema školskim predmetima, školi općenito i izvannastavnom učenju - Milovuković, Saša (Array, 2021)
The aim of this research was to determine and explain the attitudes of wannabe students of kinesiology regarding how much they like each school subject, school in general and extracurricular learning. The answers in the questionnaire were given on a semantic differential scale from 1 (100% repulsive to me) to 5 (I adore it). The study involved 63 wannabe kinesiology students who in 2021 actively prepared for the entrance exam at the Croatian Faculties of Kinesiology. The average age of the respondents was M=18.83±1.33, of which 25 girls and 38 boys. The average rating of all school subjects was M=3.14. The highest rated subject was expectedly Physical Education, but the second-best rated subject (geography) had an average rating of M=3.57. Significant difference between the rating of each school subject from the average of all school subjects was noticed in chemistry, physics and mathematics (on a negative pole compared to the average) and geography on the positive pole, with a medium to large effect size regarding the difference between arithmetic means. Extracurricular learning was almost zero correlated with all other independent variables. We can conclude that wannabe kinesiology students (aligned with other high school graduates) are not fond of school subjects, nor school in general, but this research shows they do love to learn new things not related to school, so teachers/professors might consider including extracurricular material in teaching to make prescribed material more interesting.